State and Local Government Reforms in France and Germany
268 p. 12 illus.
Keywords: The edited book aims at comparatively analysing the development and current situation of state and local government reforms in France and Germany. The articles address State and administrative traditions, intergovernmental relations, decentralisation, administrative modernisation, public finances, public sector personnel, local democracy, local (mayoral) leadership and decentral/local social policy.